The innovation of Wolbachia mosquito technology to control dengue hemorrhagic fever - Kushartanti, Roro; Wijayanti, Aprin Wahyu (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Wolbachia is a bacterium that generally occurs naturally in 50% of insect species, lives in insect cells, and is passed from one generation to the next through insect eggs. Wolbachia in the mosquito's body can inhibit the replication of the Dengue virus or other viruses. Based on the Decree of the Minister of Health of the Republic of Indonesia Number 1341 concerning the Implementation of the Pilot Project for the Implementation of Wolbachia as a Dengue Management Innovation, the application of this technology was carried out in five cities, namely Semarang City, West Jakarta, Bandung City, Kupang City, and Bontang City. The effectiveness of Wolbachia itself has been proven and researched since 2011, when it was conducted in Yogyakarta. As a result, Wolbachia was proven to reduce dengue fever cases by up to 77% and reduce the proportion of hospital admissions by 86%. This method of spreading Wolbachia mosquitoes in several cities will reduce local transmission of infection in those areas. This reduction in local transmission of dengue infection occurs both in the rainy and dry seasons. Scientifically, the success of the Wolbachia method is apparent, but the controversy is due to confused information circulating, giving rise to concern among the public. Vector control using Wolbachia is an alternative disease control method that uses mosquito vectors and is quite effective. However, the application of Wolbachia in the community must be monitored continuously to determine its impact on humans, local mosquitoes, and the ecosystem.